Modelling and sliding mode control of a wireless power transfer system for BEV charger. (13th October 2020) - Lassioui, Abdellah; Fadil, Hassan El; Rachid, Aziz; El-Idrissi, Zakariae; Bouanou, Tasnime; Belhaj, Fatima Zahrae; Giri, Fouad
In this paper, a unidirectional wireless power transfer (WPT) system for battery electric vehicle (BEV) charger is addressed. Firstly, a detailed analysis is given focusing on the following points: (i) phase shift control technique, (ii) reactive power compensation topologies and (iii) total harmonic distortion analysis. Secondly, a mathematical model is established for the studied system and its stability is discussed. It was found that the system presents an unstable behaviour when the voltage across the load is chosen as the system output. This non-minimum phase feature is dealt with using an indirect control strategy. Thirdly, based on the derived mathematical model, a non-linear controller using sliding mode control technique is developed. The control objectives are twofold: (i) tight regulation of the output load voltage and (ii) asymptotic stability of the closed loop system. It is shown using theoretical analysis and simulation that the proposed controller meets all objectives.